Penerapan Metode Mind Mapping Menggunakan Aplikasi Draw.Io Terhadap Pemahaman Konsep pada Mata Pelajaran Teknologi Informasi & Komunikasi di MA Negeri 1 Kuningan (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine students' understanding of concepts by using the Mind Mapping method using Draw.io application in the subject of Information and Communication Technology at MA Negeri 1 Kuningan. The method used used a quantitative approach with the type of quasi-experimental method with a pretest-posttest control group design. The sample used in this study was divided into 2 classes (experimental and control) with a total of 62 students. The data collection technique used is using tests/questions and questionnaires. The data analysis techniques used were validity tests, reliability tests, normality tests, homogeneity tests, hypothesis tests (t tests). This study aims to determine students' understanding of concepts by using the Mind Mapping method using Draw.io application in the subject of Information and Communication Technology at MA Negeri 1 Kuningan. The method used used a quantitative approach with the type of quasi-experimental method with a pretest-posttest control group design. The sample used in this study was divided into 2 classes (experimental and control) with a total of 62 students. The data collection technique used is using tests/questions and questionnaires. The data analysis techniques used were validity tests, reliability tests, normality tests, homogeneity tests, hypothesis tests (t tests). The results of this study show that the results of the application of the mind mapping method using the application draw.io there is a significant difference, as evidenced by the results of the research, students are able to understand the material presented. There was an increase in student understanding as seen from the average of the previous year